The Effect of Islamic Storytelling Audiovisual Therapy on Anxiety Levels in Preschool-Aged Children at Inche Abdoel Moeis Regional General Hospital, Samarinda - Rona Mika; Ni Wayan Wiwin Asthiningsih; Fatma Zulaikha (Department of Publication of Inspirasi Elburhani Foundation Desa. Pamokolan, Kecamatan Cihaurbeuti, Kabupaten Ciamis, Provinsi Jawa Barat, Indonesia, 2026)
Background & Objective: Hospitalization frequently triggers anxiety in preschool children due to unfamiliar environments, separation from parents, and exposure to medical procedures that may be perceived as frightening. Anxiety can negatively affect children’s emotional responses, cooperation during care, and recovery process. Therefore, non-pharmacological nursing interventions that are safe and appropriate to the child’s developmental stage are needed. This study aims to analyze the effect of Islamic storytelling audio-visual therapy on anxiety levels in hospitalized preschool children. Method: This study employed a pre-experimental research design using a one group pretest-posttest approach. The population consisted of preschool children undergoing hospitalization at Inche Abdoel Moeis Regional General Hospital, Samarinda, with a total sample of 16 respondents selected through purposive sampling. Data were collected using an anxiety assessment instrument before and after the intervention. Data analysis was conducted using the Wilcoxon Signed Rank Test due to non-normal data distribution. Result: The findings showed that the mean anxiety score decreased from 25.56 before the intervention to 21.68 after the intervention, with a significant value of 0.002. This shows a statistically significant reduction in anxiety levels following the intervention. Conclusion: Islamic storytelling audio-visual therapy has a significant effect in reducing anxiety levels among preschool children during hospitalization and can be considered an effective non-pharmacological nursing intervention.